Efficacy of Chinese patent medicine for primary osteoporosis: A network meta-analysis. (August 2021) - Zhao, Jinlong; Zeng, Lingfeng; Wu, Ming; Huang, Hetao; Liang, Guihong; Yang, Weiyi; Pan, Jianke; Liu, Jun
Abstract: Background and purpose: Chinese patent medicines (CPMs) have gained increasing attention for the treatment of primary osteoporosis (POP), but there is a lack of high-quality evidence regarding their efficacy. We conducted a network meta-analysis that considered both direct and indirect comparisons to assess and rank the efficacy and safety of CPMs for POP. Methods: Seven electronic databases were searched from their inception to May 2020. A random effects model was applied within a frequentist framework. Results: Thirty-eight studies with 16 kinds of medicines (13 CPMs, 3 Western medicines) and 3, 941 patients were included in this study. This study showed that Jintiange capsule was the most efficacious for increasing the L2-L4 average bone mineral density (BMD) and that Zuogui Wan was the most efficacious for increasing the femoral neck BMD. Compared with calcium, Gusongjiangu Wan (RR = 10.04, 95% CI 1.36–74.32, p = 0.008), Gushukang granules (RR = 12.63, 95% CI 2.02–78.99, p = 0.015) and Xianling Gubao capsule (RR = 6.06, 95% CI 1.38–26.65, p = 0.0003) had fewer adverse reactions. Conclusion: In the treatment of POP, Jintiange capsule and Zuogui Wan are effective CPMs for improving the BMD of the lumbar spine and femoral neck, respectively. Highlights: Jintiange capsule was the most effective medicine for improving the bone mineral density of the lumbar vertebrae. For improving the bone mineral density of the femoral neck, Zuogui Wan had better efficacy. Compared with calcium, Gusongjiangu Wan, Gushukang granules and Xianling Gubao capsule had fewer adverse reactions.